Fluorescent in situ hybridization has limitations in screening NRG1 gene rearrangements - Xiaomei Zhang; Lin Li; Fuping Gao; Binbin Liu; Jing Li; Shuang Ren; Shuangshuang Peng; Wei Qiu; Xiaohong Pu; Qing Ye (BMC, 2024)
Abstract Background NRG1 fusion is a promising therapeutic target for various tumors but its prevalence is extremely low, and there are no standardized testing algorithms for genetic assessment. Mothods In this study, we analyzed 3008 tumors using Fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC) to screen for NRG1 translocation and p-HER3 expression. Results Our results demonstrated no cases with p-HER3 positivity through IHC. Nonetheless, 29 cases (0.96%) were identified positive for NRG1 translocation through FISH, with three different signal types. FISH-positive cases were subsequently subjected to next-generation sequencing (NGS) testing. However, only eight of these cases were confirmed with NRG1 fusion through NGS. Notably, we divided FISH into three types and FISH type C group was consistent with NGS results. All NGS NRG1 fusion tumors were adenocarcinomas, with a higher prevalence in females. Our findings indicate that although FISH has limitations in screening NRG1 gene rearrangements, NRG1 fusions can be reliably detected with signals exhibiting low copy numbers of the 5'-end of the gene and no fusion signals. Conclusion Considering the high cost of NGS, FISH remains a useful method for screening NRG1 fusions in various types of tumors. This study provides valuable insights into the molecular mechanisms of NRG1 fusion and identifies potential treatment targets for patients suffering from this disease.